2010
DOI: 10.1021/jo1015757
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Ligation of S-Scylated Cysteine Peptides to Form Native Peptides via 5-, 11-, and 14-Membered Cyclic Transition States

Abstract: Cysteine-containing dipeptides 3a-l, (3b+3b') (compound numbers in parentheses are used to indicate racemic mixtures; thus (3b+3b') is the racemate of 3b and 3b'), and tripeptide 13 were synthesized in 68-96% yields by acylation of cysteine with N-(Pg-α-aminoacyl)- and N-(Pg-α-dipeptidoyl)benzotriazoles (where Pg stands for protecting group in the nomenclature for peptides throughout the paper) in the presence of Et(3)N. Cysteine-containing peptides 3a-l and 13 were S-acylated to give S-(Pg-α-aminoacyl)dipepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…The presence of a disulfide linkage between the cysteine residues was also supported by the chemical shifts of the C β carbons at δ C 40.3 and 40.0, which were similar to those of other peptides possessing cysteines with a similar disulfide linkage [12]. For comparison, the shifts of free cysteine and cysteic acid were approximately δ C 25.5 and 50, respectively [13,14]. Thus, chujamide A ( 1 ) was determined to be a novel cyclic cystine bridged dodecapeptide.…”
Section: Resultsmentioning
confidence: 76%
“…The presence of a disulfide linkage between the cysteine residues was also supported by the chemical shifts of the C β carbons at δ C 40.3 and 40.0, which were similar to those of other peptides possessing cysteines with a similar disulfide linkage [12]. For comparison, the shifts of free cysteine and cysteic acid were approximately δ C 25.5 and 50, respectively [13,14]. Thus, chujamide A ( 1 ) was determined to be a novel cyclic cystine bridged dodecapeptide.…”
Section: Resultsmentioning
confidence: 76%
“…Katritzky et al have demonstrated the utilization of Fmoc-N-protected C-terminal-Bt amino acids in the NCL synthesis of dipeptides containing cysteine. [24,25] Additional approaches have been developed to generate active esters through the formation of C-terminus-Bt peptides.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported ligations of S-acylated Cys-containing peptides to form the corresponding native peptides through long-range chemical ligations via 8-to 19-membered transition states. [24][25][26][27][28] This methodology utilizes the selective Sacylation of Cys-containing peptides by N-acyl benzotriazoles followed by microwave-assisted high-yielding chemical ligations of the resulting S-acyl isopeptides under mild conditions and with no auxiliary groups. However, the low abundance of Cys in the natural peptide sequence remains an obstacle.…”
Section: Introductionmentioning
confidence: 99%